Characterization of mango (Mangifera indica) varieties for pickle making (Current Horticulture, 2024)
An experiment was conducted on characterization of mango (Mangifera indica L.) varieties using morphological characters for selection of best pickle varieties for pickle making, at Horticultural Research Station, Ananthrajupet, Andhra Pradesh during 2015-16. Eleven mango varieties were characterized morphologically for fruit and stone characters. The bigger fruit-sized was seen in Gaddemar, while smaller-sized fruits were in Alipasand and Amrigola. Other collections exhibited medium-sized fruits. Gaddemar showed maximum fruit weight (936.2g), fruit width (111.19 mm) and pulp thickness (1.68 mm), whereas Amrigola exhibited lowest fruit weight (76.5g), fruit width (52.26 mm) and pulp thickness (10.20 mm). The mango variety, Chilaka Mukku showed highest TSS (14.6° Brix) and minimum TSS in Alipasand (6.5° brix). Peddarasam showed maximum stone weight (102.5g) and lowest stone weight in Amrigola (8.0g). Gaddemar showed highest fiber length (16.72 mm) while least fiber length (2.8 mm) was noted in Peddarasam. Gaddemar and Alipasand were identified for pickle making due to higher acidity, presence of fibre and lower TSS values.
Keywords: Acidity; Morphological characters; Fibre; Pickle; TSS; Stone weight; Pulp